KOMPARASI MODEL PEMBELAJARAN KOOPERATIFTIPENUMBERED HEADS TOGETHER (NHT) DENGAN MODEL PEMBELAJARANPENDEKATAN SAINTIFIK TIPEPROBLEM BASEDLEARNING (PBL) PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA SISWAKELASXTEKNIK AUDIO - Rizky Almanda; Thamrin Thamrin; Hanesman Hanesman (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
The pusposes of research to find out learning result using cooperative learning model of type Numbered Heads Together (NHT) with scientific approach learning model of type Problem Based Learning (PBL), specially on Basic electricity and electronics Subjects at SMK Negeri 1 Sumbar. This is probably because in the learning process students are less active and less participate in teaching. This research is a quasi experimental study with pretest-posttest control group design. Experimental I class used cooperative learning model of Numbered Heads Together (NHT) and Experimental II class used scientific approach learning model of Problem Based Learning (PBL). The results of study have shown that average of the experimental I class test result is 83,13 while the Experimental II class has provided the average outcome of  78,29. However, this learning shows that there is a significant effect of student’s learning outcome between the usage of cooperative learning model of typeNumbered Heads Together (NHT)rather than scientific approach learning model of type Problem Based Learning (PBL)on Basic electricity and electronics subject. The hypothesis test(t-test) shows that tc> tt( 2.12 > 2.05). Therefore,applying cooperative learning model of type Numbered Heads Together (NHT) is more effective than scientific approach learning model of type Problem Based Learning (PBL) .Keywords: Numbered Heads Together, Problem Based Learning, Learning Outcomes